Strategi Komunikasi Yayasan Tukad Bindu untuk Membangun Awareness sebagai Obyek Ekowisata Perkotaan - Makalam, Diandra Annisa; Purnawan, Ni Luh Ramaswati; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2021)
As an urban ecotourism object in Denpasar City, Tukad Bindu has a responsibility in spreading awareness to the local residents about the importance of environmental conservation. This research has a goal to spread the awareness of Tukad Bindu as an urban ecotourism object by composing a communication strategy. This is a descriptive qualitative type of research, using two data collection techniques such as interviews and documentation. The outcome of this study indicate that the Tukad Bindu Foundation seeks to build awareness through informative and educational communication techniques in the form of workshops, community service, etc. In addition, the Tukad Bindu Foundation also utilizes social media in the form of Instagram and Facebook as a channel to deliver the information and education about Tukad Bindu. Keywords: Tukad Bindu Foundation, Awareness, Communication Strategy